Royal Police Ordinances in Early Modern Sweden : the Emergence of Voluntaristic Understanding of Law. - Kotkas, Toomas (Northern world, 2013)
In Royal Police Ordinances in Early Modern Sweden, based on analysis of a large amount of empirical material Toomas Kotkas claims that a new, voluntaristic understanding of law emerged in 17th-century Sweden.